Antiasthma Activities of Moringa oleifera Lam. Leaves Extract on the Eosinophil Count and Mast Cells in BALB/c Mice - Dian Arsanti Palupi; Tri Wahyuni Prasetyowati; Dwi Murtiningsih; Dede Mahdiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Asthma is a chronic inflammation of the respiratory tract. This study aimed to prove Moringa oleifera Lam. leaves extract's effect on reducing the eosinophil count and mast cells in asthmatic mice. Twenty BALB/c mice that met the inclusion criteria were divided into four groups of standard control (K1), negative control (K2), dexamethasone (K3), and M. oleifera leaves extract (K4). On days 0 and 7, intraperitoneal ovalbumin (OVA) was sensitized. On days 14, 16, and 18, mice were re-sensitized by inhalation using 1% OVA in sterile 0.9% NaCl. On days 18 to 25, K1 and K2 groups were given Na-CMC, the K3 group was given dexamethasone 1.3 µg/day, and the K4 group was given M. oleifera leaves extract 3.9 mg/day. On the 25th day, the mice were terminated to analyze the eosinophil count and stable bronchiolar mast cells. In conclusion, M. oleifera leaves extract was proven to decrease the eosinophil count with a p-value <0.05 and could stabilize bronchiolar mast cells with a p-value <0.05.